Anxiety disorder burden inequalities across middle- and high-income countries: 1990–2035 trends and projections - Yuxuan He; Lijie Liu; Wenfu Song; Yuxi Li; Yimeng Gao; Wenwen Zhu; Runru Mai; Fei Tan; Fuping Xu; Zhimin Yang (PLoS ONE, 2026)
Background Anxiety disorders are among the most common mental health conditions worldwide, but their burden varies substantially across countries with different income levels. Evidence remains limited on how anxiety disorder burden, violence-related risk factors, and future trends differ across middle- and high-income countries (MHICs). This study examined inequalities in the burden of anxiety disorders across MHICs from 1990 to 2023, quantified the burden attributable to major risk factors, and projected prevalence trends to 2035. Methods Data on incidence, prevalence, and disability-adjusted life years (DALYs) for anxiety disorders were obtained from the Global Burden of Disease 2023 database. We estimated counts, age-standardized incidence rates (ASIRs), age-standardized prevalence rates (ASPRs), and age-standardized DALY rates (ASDRs), with 95% uncertainty intervals (UIs), by income group, sex, age, country, and year. Risk-attributable DALYs were assessed for intimate partner violence (IPV), bullying victimization (BV), and sexual violence against children (SVAC). Temporal trends were evaluated using Joinpoint regression, and Bayesian age-period-cohort (BAPC) models were used to project prevalence rates to 2035. Results In 2023, MHICs accounted for 91.3% (95% UI 60.7–137.2) of global prevalent cases, 90.8% (95% UI 50.4–153.7) of incident cases, and 91.2% (95% UI 44.8–177.6) of anxiety disorder DALYs. High-income countries (HICs) had the highest ASIRs, ASPRs, and ASDRs, whereas lower-middle-income countries (LMICs) had lower rates but larger absolute numbers of cases. From 1990 to 2023, the burden increased across MHICs, with the fastest growth observed in LMICs. Females had consistently higher ASIRs, ASPRs, and ASDRs than males, and the highest burden was observed among children and adolescents. IPV, BV, and SVAC were associated with substantial anxiety disorder DALYs, with marked differences by income group, age, and sex. BAPC projections suggested that prevalence rates may continue to increase through 2035, particularly among females and in lower-income settings. Conclusions Anxiety disorder burden remains high and unequally distributed across MHICs. The burden is characterized by persistent differences by income group, sex, and age, and is associated with violence-related risk factors. These findings support the need for income-sensitive, gender-responsive, and age-targeted mental health strategies, with particular attention to prevention of violence-related risks and improved access to mental health services in lower-income settings.